Two dimensional modeling of helical structures, an application to simple strands. (1st October 2016) - Karathanasopoulos, Nikolaos; Kress, Gerald
Abstract: Herein, we elaborate a generic, planar finite element model for the simulation of the mechanical response of helical structures to axial and torsional strain. We verify the modeling approach over a wide range of helix angles using closed-form expressions. Thereafter, we present a case study application addressing the structural response of single layer engineering strands. Finally, we analyze the model's computational merits.